Improving Expressive Language Abilities Through Storytelling Activities (The Mouse Hare And The Crocodile) In Early Childhood In Class B Of Islahul Ummah Kindergarten In The 2024/2025 Academic Year - Sulfianingsih, Dende; Arzani, M.; Ramzi, Muhajirin (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to determine the level of the learning process using storytelling activities on children's language skills and to determine the level of children's ability in using storytelling activities to improve expressive language skills in TK Islahul Ummah, Dusun Cupek, Sigar Penjalin Village, Tanjung District, Academic Year 2024/2025. The subjects of this study were 23 group B children in TK Islahul Ummah, consisting of 15 boys and 8 girls. The research used a classroom action research approach based on the Kemmis and Taggart model, which consists of the stages of planning, action implementation, observation, and reflection. Data were collected through observation and analyzed using the classical completeness formula, which must reach 80%. The study was carried out in two cycles: cycle I was conducted in three meetings, while cycle II was conducted in two meetings, with each meeting designed to stimulate children's language skills through listening, imitating, and orally retelling story content. Based on observations and data analysis in each cycle, a significant improvement was found in children's expressive language skills, in terms of vocabulary, sentence structure, and speaking confidence. The final results showed that continuous and creative storytelling activities can optimally improve children's expressive language skills at TK Islahul Ummah.The research results show that the storytelling activity